ASP.NET 1.1 Solutions Toolkit - MacDonald, Matthew; Garcia Aprea, Victor; Dewson, Robin; Nandu, Saurabh; Delorme, Richard; Cazzulino, Daniel; Ferracchiati, Fabio Claudio; Gottlieb, David; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2005)
This collection of reusable ASP.NET components serves two purposes. First, the components are ready to use, so you may add exciting features to your own ASP.NET websites. Second, each component's design and implementation is discussed, and you'll discover tips and tricks applicable for developing your own controls. Controls can be cut and pasted or used as templates for you to build your own controls. And the 15 included controls (programs) cover a broad range of situations, providing you both working coded solutions to your problem and the rationalization behind those solutions. Overall, this highly anticipated book provides immediate solutions to range of common problems.
Control Development -- Spinner Control -- Bindable Bullet List -- Data Navigator -- File Uploader -- Globalizable Page -- Validation Control -- Image Magnifier -- Chart -- Image Map Generator -- Reviewing Controls -- Straw Poll -- RSS Reader -- Search Engine.
Keywords: Microsoft software; Microsoft .NET Framework; Software engineering; Microsoft and .NET.; Software Engineering/Programming and Operating Systems